Nutritional and dietary interventions for the treatment of Chronic Fatigue Syndrome - Monika Prylińska; Jakub Husejko; Natalia Skierkowska; Daria Bieniek; Marcin Kożuchowski; Mateusz Porada; Weronika Topka; Mateusz Modrzejewski; Mariusz Wąsicki; Oktawia Wysocka; Kornelia Kędziora-Kornatowska (Journal of Education, Health and Sport, 2018)
Background: Chronic fatigue syndrome is an increasingly frequent disorder characterized by prolonged fatigue and few specific symptoms. He favors prolonged stress and life in a constant hurry. The main symptoms of chronic fatigue include: headache, throat, myalgia, joint pain, short-term memory impairment, sleep disorders, malaise occurring after physical exertion and lasting over 24 hours, and painful lymph nodes. The possibility of chronic fatigue syndrome should be considered in patients with the above symptoms, if they persist for more than 6 months. In this review, we wanted to focus on the possibilities to minimize the symptoms of chronic fatigue syndrome through nutritional and dietary intervention. Materials and methods: Analysis of articles in the EBSCO and Google Scholar database using keywords: Chronic Fatique Syndrome, nutritional, dietary interventions, treatment. Results: Patients with chronic fatigue syndrome suffer from chronic fatigue and not specific symptoms, which makes diagnosis difficult. The analysis of articles shows that dietary and nutritional interventions tailored to the patient reduce the feeling of fatigue, which is the main problem among patients with chronic fatigue syndrome. Positive effects in the form of alleviation of symptoms have been observed while using, inter alia: polyphenols, L-carnitine, probiotics, CoQ10 and NADH and GAA. Conclusions: Dietary and nutritional intervention has a positive effect on intestinal microflora, intestinal mucosa, oxidative stress and proper functioning of mitochondria, thanks to which it reduces symptoms of chronic fatigue syndrome. Individual and appropriate supplementation depending on the etiology of the syndrome can lead to relief of symptoms.